(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The new mode of instability found by Tunney et al. [24] is studied with viscous stability theory in this article. When the high-speed boundary layer is subject to certain values of favorable pressure gradient and wall heating, a new mode becomes unstable due to the appearance of the streamwise velocity overshoot (U(y) > U_∞) in the base flow. The present study shows that under practical Reynolds numbers, the new mode can hardly co-exist with the conventional first mode and Mack's second mode. Due to the requirement for additional wall heating, the new mode may only lead to laminar-turbulent transition under experimental (artificial) conditions.